THE RELATION BETWEEN SMARTPHONE USAGE IN CHANGES OF OCULAR BIOMETRY COMPONENTS AND REFRACTION AMONG ELEMENTARY SCHOOL CHILDREN: Oral Presentation - Observational Study - Ophthalmologist - MARCO ANGELO LIWAN; MARLYANTI NUR RAHMAH; HABIBAH SETYAWATI MUHIDDIN; FIRDAUS KASIM; NOOR SYAMSU; AHMAD ASHRAF AMALIUS (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Digital media is currently being increasingly used in recent years. The development of the visual system begins as soon as a child is born through visual stimulation and interaction with the environment that develops comprehensively with the general development of children. Smartphone usage affects eye developmental process. Explain the effect of ocular biometry components and refraction change in elementary school children due to duration of smartphone usage Methods : A one-year cohort prospective study was taken on 6-8-year-old children in the selected elementary school in South Sulawesi, Indonesia divided into two groups focused on the duration of smartphone usage and its relationship to changes in ocular biometric components and refraction. Results : The ocular biometry will develop in 6 and 12 months. The axial length, corneal diameter, keratometry, central corneal thickness, anterior chamber depth increased, spherical equivalent experienced a myopic shift, while the lens thickness decreased. Smartphone usage of more 3 hours had a significant difference compared to smartphone usage less than 3 hours in changes in the axial length of the eyeballs at 6 and 12 months, spherical equivalent on examination 12 (p<0.05), while other tests were not significant (p>0.05). Conclusion : Smartphone usage more than three hours per day will cause a significant change in ocular biometry and refraction